The Harvard Classics volume 13 - Eliot, Charles W. (PF Collier& Son New York, 1910)
Fifteen minutes a day; the reading guide. New York, Collier [1956, c1938] 95 p.: illus.; 23 cm.; V. 30--Scientific papers: physics, chemistry, astronomy, geology.; V. 31--The autobiography of Benvenuto Cellini.; V. 32--Literary and phylosophical essays, French, German, Italy.; V. 33--Voyages and travels, ancient and modern.; V. 34--French and English philosophers: Descartes, Rousseau, Voltaire, Hobbes.; V. 35--Chronicle and romance: Froissart, Malory, Holinshed.; V. 36--The prince, by N. Machiavelli. Utopia, by T. More. Ninety-four theses, Address to the German nobility, and Concerning Christian liberty; by M. Luther.; V. 37--English philosophers of the seventeenth and eighteenth centuries.; V. 38--Scientific papers: physiology, medicine, surgery, geology.; V. 39--Prefaces and prologues to famous books.; V. 43--American historical drama.; V. 48--Thoughts, Letters, and Minor works; by B. Pascal.; V. 49--Epic and saga.; V. 50--The Harvard classics. (Indexes).; V. 51--Lectures on The Harvard classics, edited by W.A. Neilson.
t